PODER E FRAGMENTAÇÃO NA MODERNIDADE RELIGIOSA: UMA ANÁLISE DA ATOMIZAÇÃO NEOPENTECOSTAL EM SOROCABA - Oliveira, Sérgio Francisco dos Santos (2009)
This work analyses a fragmentation which is occurring in neopentecostalism, trying to investigate the relationship between the reasons of such fragmentation and the specific ways by wich Pentecostal groups establish themselves in modernity, above all in their concepts of power and in the forms of their structure. This inquiry was done in dialogue with the theory of secularization and of modern power, and is empirically founded on qualitative research, done in interviews with leaders of neopentecostal churches in the city of Sorocaba. Developing this kind of analysis, it is demonstrated how these religious expressions represent an adaptation to the environment of Brazilian modernity and modern culture, especially by the assimilation of popular beliefs and practices, and through the culture of marketing. And it is in this connection between the form of exercise of Power and modern cultural, political and economic contexts, that one finds the explanation of this accentuated neopentecostal fragmentation.(AU)